(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Hemolytic anemias occur due to the predominance of erythrocyte destruction over formation. In hemolytic anemia, the life span of erythrocytes is reduced to 12-14 days and pathological hemolysis occurs.